The red badge of courage - Coleman, Wim.; Crane, Stephen 1871-1900. (Logan, Iowa Perfection Learning, 1993)
During his service in the Civil War a young Union soldier matures to manhood and finds peace of mind as he comes to grips with his conflicting emotions about war.
Keywords: Chancellorsville, Battle of, Chancellorsville, Va., 1863 -- Juvenile fiction; Chancellorsville (Va.), Battle of, 1863 -- Fiction; United States -- History -- Civil War, 1861-1865 -- Fiction